Akulturasi Islam Dalam Tradisi Mappasikarawa di Kabupaten Luwu; Tinjauan Hukum Islam - A Nur'aini; Fasiha Kamal; Hamzah K; Rukman A R Said; Yusmita Yusmita (Palita: Journal of Social Religion Research, 2023)
The focus of his research is how is the acculturation of Islam in the mappasikarawa tradition and the perspective of Islamic law on the values of the mappasikarawa tradition. This study was designed with qualitative research using a sociological approach, observation, interview, and documentation data collection techniques. The results of this study indicate that implementing the mappasikarawa tradition has experienced acculturation, including acculturation of Islam, where prayers in the form of mantras in local languages have been replaced with prayers in Islam. Islamic values contained in the mappasikarawa process are reading a prayer before doing the mappasikarawa by using Arabic as the language, which is symbolized as the language of the Islamic religion because it is the language of the Koran, which is the holy book of Muslims.